Triumph of Avicennism. Reflections on Gutas, D. (2020). Orientations of Avicenna’s Philosophy. Essays on his Life, Method, Heritage. London [etc.]: Routledge. - Yakubovych, Mykhaylo (Sententiae, 2021)
Review of Gutas, D. (2020). Orientations of Avicenna’s Philosophy. Essays on his Life, Method, Heritage. London [etc.]: Routledge.